2022
DOI: 10.1126/sciadv.abl9478
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free carbocatalyst for room temperature acceptorless dehydrogenation of N-heterocycles

Abstract: Catalytic dehydrogenation enables reversible hydrogen storage in liquid organics as a critical technology to achieve carbon neutrality. However, oxidant or base-free catalytic dehydrogenation at mild temperatures remains a challenge. Here, we demonstrate a metal-free carbocatalyst, nitrogen-assembly carbons (NCs), for acceptorless dehydrogenation of N-heterocycles even at ambient temperature, showing greater activity than transition metal–based catalysts. Mechanistic studies indicate that the observed catalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…44–46 Subsequent isomerization of 3,4-dihydroquinoline generates 1,2-dihydroquinoline ( 3 ). 47 Then, the dehydrogenation of 1,2-dihydroquinoline ( 3 ) to quinoline ( 4 ) occurs, similar to the dehydrogenation of 1,2,3,4-tetrahydroquinoline to 3,4-dihydroquinoline. At the same time, the catalytic hydrogenation of nitrobenzene ( 5 ) generates nitrosobenzene ( 6 ) and a molecule of water.…”
Section: Resultsmentioning
confidence: 93%
“…44–46 Subsequent isomerization of 3,4-dihydroquinoline generates 1,2-dihydroquinoline ( 3 ). 47 Then, the dehydrogenation of 1,2-dihydroquinoline ( 3 ) to quinoline ( 4 ) occurs, similar to the dehydrogenation of 1,2,3,4-tetrahydroquinoline to 3,4-dihydroquinoline. At the same time, the catalytic hydrogenation of nitrobenzene ( 5 ) generates nitrosobenzene ( 6 ) and a molecule of water.…”
Section: Resultsmentioning
confidence: 93%
“…6,7 Based on the reversible chemical hydrogen storage mechanism (hydrogenation/dehydrogenation cycle of unsaturated organic liquids), the purity of released hydrogen reaches 99.99%, which meets the demand of on-board hydrogen source systems. 8,9 Among various LOHC molecules, the N-ethylcarbazole vs dodecahydro-N-ethylcarbazole (NECZ vs 12H-NECZ) cycle system offers a desirable candidate with a high hydrogen gravimetric capacity (5.79 wt %) and a relatively low reaction temperature. 10−13 For such a structure-sensitive reaction, noble metal catalysts (e.g., Pd and Pt) have shown good catalytic performance toward dehydrogenation of 12H-NECZ at a relatively benign temperature (below 200 °C).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Compared with several hydrogen storage technologies ( e.g. , pressurized liquid hydrogen, metal hydrides, and nanomaterials), the liquid organic hydrogen carrier (LOHC) provides a promising route for large-scale hydrogen storage and transportation with advantages of high gravimetric capacity, convenient usability, and infrastructure compatibility. , Based on the reversible chemical hydrogen storage mechanism (hydrogenation/dehydrogenation cycle of unsaturated organic liquids), the purity of released hydrogen reaches 99.99%, which meets the demand of on-board hydrogen source systems. , …”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been demonstrated that iron (Fe) could achieve dehydrogenation of THQ in 18 h at 145 °C, but at a lower yield (88 %) than that obtained by precious metals, [10] while nitrogen assembly carbons can achieve > 99 % yield at 150 °C in 4 h or at room temperature in five days. [11] From a sustainability perspective, a more energy-efficient acceptorless dehydrogenation process relies on the photo activation of the catalyst. [12] Metal-organic frameworks (MOFs) with narrow distance between their active sites have been shown to catalyze the dehydrogenation of THQ in 3 h under ultraviolet (UV) illumination (390 nm).…”
Section: Introductionmentioning
confidence: 99%
“…Non‐precious metal catalysts have also been investigated to overcome the high cost of the precious metals. For example, it has been demonstrated that iron (Fe) could achieve dehydrogenation of THQ in 18 h at 145 °C, but at a lower yield (88 %) than that obtained by precious metals, [10] while nitrogen assembly carbons can achieve >99 % yield at 150 °C in 4 h or at room temperature in five days [11] …”
Section: Introductionmentioning
confidence: 99%